Diversity of Molecular Mechanisms Conferring Carbapenem Resistance to Pseudomonas aeruginosa Isolates from Saudi Arabia. (11th August 2016) - Al-Agamy, Mohamed H.; Jeannot, Katy; El-Mahdy, Taghrid S.; Samaha, Hassan A.; Shibl, Atef M.; Plésiat, Patrick; Courvalin, Patrice
Abstract : Background. This study described various molecular and epidemiological characters determining antibiotic resistance patterns in Pseudomonas aeruginosa isolates. Methods. A total of 34 carbapenem-resistant P. aeruginosa clinical isolates were isolated from samples collected at a tertiary hospital in Riyadh, Saudi Arabia, from January to December 2011. Susceptibility testing, serotyping, molecular characterization of carbapenem resistance, and pulsed-field gel electrophoresis (PFGE) were performed. Results. All isolates were resistant to ceftazidime, and more than half were highly resistant (minimum inhibitory concentration (MIC) > 256 mg/L). Fifteen isolates had MIC values ≥64 mg/L for any of the carbapenems examined. Vietnamese extended-spectrum β -lactamase (VEB-1) (n = 16 / 34 ) and oxacillinase (OXA-10) (n = 14 / 34 ) were the most prevalent extended-spectrum β -lactamase and penicillinase, respectively. Verona imipenemase (VIM-1, VIM-2, VIM-4, VIM-11, and VIM-28) and imipenemase (IMP-7) variants were found in metallo- β -lactamase producers. A decrease in outer membrane porin gene ( oprD ) expression was seen in nine isolates, and an increase in efflux pump gene ( MexAB ) expression was detected in five isolates. Six serotypes (O:1, O:4, O:7, O:10, O:11, and O:15) were found among the 34 isolates. The predominant serotype was O:11 (16 isolates), followed by O:15 (nine isolates). PFGE analysis of the 34 carbapenem-resistant P. aeruginosa isolates revealed 14 different pulsotypes. Conclusions. These results revealed diverse mechanisms conferring carbapenem resistance to P. aeruginosa isolates from Saudi Arabia.